Effect of a collector bag for measurement of postpartum blood loss after vaginal delivery: Cluster randomised trial in 13 European countries - Zhang, W; Deneux-Tharaux, C; Brocklehurst, P; Juszczak, E; Joslin, M; Alexander, S (2010)
Objective: To evaluate the effectiveness of the systematic use of a transparent plastic collector bag to measure postpartum blood loss after vaginal delivery in reducing the incidence of severe postpartum haemorrhage. Design: Cluster randomised trial. Setting: 13 European countries. Participants: 78 maternity units and 25 381 women who had a vaginal delivery. Interventions: Maternity units were randomly assigned to systematic use of a collector bag (intervention group) or to continue to visually assess postpartum blood loss after vaginal delivery (control group). Main outcome measures: The primary outcome was the incidence of severe postpartum haemorrhage in vaginal deliveries, defined as a composite of one or more of blood transfusion, intravenous plasma expansion, arterial embolisation, surgical procedure, admission to an intensive care unit, treatment with recombinant factor VII, and death. Results: Severe postpartum haemorrhage occurred in 189 of 11 037 of vaginal deliveries (1.71%) in the intervention group compared with 295 of 14 344 in the control group (2.06%). The difference was not statistically significant either in individual level analysis (adjusted odds ratio 0.82, 95% confidence interval 0.26 to 2.53) or in cluster level analysis (difference in weighted mean rate adjusted for baseline rate 0.16%, 95% confidence interval -0.69% to 1.02%). Conclusion: Compared with visual estimation of postpartum blood loss the use of a collector bag after vaginal delivery did not reduce the rate of severe postpartum haemorrhage. Trial registration: Current Controlled Trials ISRCTN66197422.